Association between postoperative pathological results and non-sentinel nodal metastasis in breast cancer patients with sentinel lymph node-positive breast cancer - Lingguang Dong; Suosu Wei; Zhen Huang; Fei Liu; Yujie Xie; Jing Wei; Chongde Mo; Shengpeng Qin; Quanqing Zou; Jianrong Yang (World Journal of Surgical Oncology, 2024)
Abstract Objective For patients with 1–2 positive sentinel lymph nodes (SLN) identified by biopsy, the necessity of axillary lymph node dissection (ALND) remains a matter of debate. The primary aim of this study was to investigate the association between postoperative pathological factors and non-sentinel lymph node (NSLN) metastases in Chinese patients diagnosed with sentinel node-positive breast cancer. Methods This research involved a total of 280 individuals with SLN-positive breast cancer. The relationship between postoperative pathological variables and non-sentinel lymph node metastases was scrutinized using univariate, multivariate, and stratified analysis. Results Among the 280 patients with a complete count of SLN positives, 126 (45.0%) exhibited NSLN metastasis. Within this group, 45 cases (35.71%) had 1 SLN positive, while 81 cases (64.29%) demonstrated more than 1 SLN positive. Multivariate logistic regression analysis revealed that HER2 expression status (OR 2.25, 95% CI 1.10–4.60, P = 0.0269), LVI (OR 6.08, 95% CI 3.31–11.14, P < 0.0001), and the number of positive SLNs (OR 4.17, 95% CI 2.35–7.42, P < 0.0001) were positively correlated with NSLNM. Conclusion In our investigation, the risk variables for NSLN metastasis included LVI, HER2 expression, and the quantity of positive sentinel lymph nodes. However, further validation is imperative, including this institution, distinct institutions, and diverse patient populations.